PERAN NOTARIS PEMALSUAN AKTA BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA BARU (UU NO. 1 TAHUN 2023): The Role of Notaries in Deed Forgery Under The New Criminal Code (Law No. 1 of 2023) - Pratiwi, Ida Ayu Windhari Kusuma; Surya, I Kadek Adi; Dharma, Ida Bagus Wirya (Ganec Swara, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code marks a significant reform of Indonesia’s national criminal law system. One of the legal issues that directly affects the profession of public officials concerns the offense of falsifying authentic deeds. As public officials authorized to issue authentic deeds, notaries are particularly vulnerable to criminal allegations involving forged documents. This article aims to examine the redefinition of the offense of forgery and the limits of criminal liability imposed on notaries under the New Criminal Code. The study employs a normative juridical method using both statutory and conceptual approaches. The findings indicate that the New Criminal Code adopts a stricter and more objective formulation of the offense of authentic deed forgery. A notary should not be held criminally liable when the falsification originates from the bad faith of the appearing parties who submit forged supporting documents. Legal protection for notaries may be ensured through the strict application of the mens rea principle by law enforcement authorities. In conclusion, strengthening the formal verification process of supporting documents constitutes the primary instrument for mitigating criminal liability risks faced by notaries under the current legal framework.